(untitled) (Revista Contexto & Educação, 2026)
Through a bibliographic review of the proceedings of the Southern Regional Meeting on Biology Teaching (EREBio Sul), this study identified a lack of research addressing the clitoris in the field of biology education. Only one study was found that mentions the organ, but in a restricted way, and its authors have no academic ties to the south of the country, showing that this is not a privileged discussion among educators in the south. Based on this, we reflect on the effects of this absence in the field of education and construct indicators of pedagogical and investigative paths in the form of four clues, in order to emphasize the importance of more studies on the clitoris in biology education research.